Comparison of Emotional stability and Social Adjustment between Athletes with Mixed and Fixed Mindsets - Mrs. Ajisha Stephen G S,; Dr. C. DURAI, (The Bioscan, 2025)
Mindset refers to the beliefs and attitudes that shape how athletes handle challenges, setbacks, effort, and success. In sports, it is just as important as physical ability, because a strong mindset helps athletes stay motivated, overcome obstacles, and keep improving. Emotional stability refers to an individual’s capacity to stay composed and maintain balance under pressure, allowing quick adjustment after setbacks (Robbins & Judge, 2019). Social adjustment involves adapting to social settings, understanding accepted behaviours, and building healthy interpersonal relationships (Argyle, 2001).Athletes often possess a fixed mindset generally view their abilities as predetermined and unchangeable, often avoiding challenges and withdrawing when faced with difficulties. Conversely, athletes with a mixed mindset believe that performance can be improved through sustained effort, training, and learning. They remain motivated during demanding phases and interpret failures as learning opportunities. The present study examined whether athletes with fixed and mixed mindsets differ in their levels of emotional stability and social adjustment. A total of 72 athletes residing in different sports hostels in Thiruvananthapuram, Kerala, were assessed using the Implicit Theory of Intelligence Questionnaire developed by Carol Dweck (1999). Emotional stability and social adjustment were treated as independent variables and measured using the Emotional Maturity Scale devised by Dr. Yashvir Singh and Dr. Mahesh Bhargava (1990). An independent t-test, along with ANOVA, was conducted to assess the significance of differences between the groups. The findings indicated that there was no statistically significant difference in emotional stability or social adjustment between the two groups. Keywords Fixed Mindset, Mixed Mindset, Emotional stability and Social Adjustment.